Sodium ferric phosphate pyrophosphate positive electrode material, preparation method thereof and sodium ion battery
By covering conductive carbon and SiO2 on the surface of sodium ferric pyrophosphate positive electrode material, combining the composite carbon source and SiO2 preparation method, the problem of insufficient performance of phosphate pyrophosphate positive electrode material is solved, and the specific capacity of sodium ion batteries is significantly improved and rate performance, achieving higher cycle stability and high energy density.
Patent Information
- Application Number
- CN202411502877.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2024-12-31
AI Technical Summary
The specific capacity and rate performance of existing phosphate pyrophosphate cathode materials is low, which limits its application potential in sodium ion batteries.
The positive electrode material of sodium ferric pyrophosphate was used and the surface was coated with conductive carbon and SiO2, and prepared by vacuum drying and sintering processes. The combination of composite carbon source and SiO2 was used to improve the conductivity and cyclic stability of the material.
The specific capacity and rate performance of sodium ferric pyrophosphate positive electrode material is significantly improved, and its cycle stability and high rate performance in sodium ion batteries are enhanced. At the same time, it has the advantages of simple operation, low cost, and green environmental protection.
Smart Images

Figure CN119230791A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of sodium ion batteries, and in particular to a sodium iron pyrophosphate positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] Sodium-ion batteries, with their unique advantages of abundant resources, wide distribution and low price, not only show great application potential in large-scale energy storage equipment, but also effectively fill the gap in the current mobile energy storage market and have extremely high commercial value. In the construction of sodium-ion batteries, the positive electrode, as a core component, plays a decisive role in the cost, performance and life of the battery. Therefore, the development of new high-performance sodium-ion battery positive electrode materials has become a top priority in current research.
[0003] At present, the mainstream cathode materials for sodium-ion batteries mainly include layered transition metal oxides, Prussian blue analogs, and polyanionic compounds. However, these materials all have their own limitations. Layered transition metal oxides have the defects of poor cycle performance and high cost; Prussian blue analogs face the challenges of low specific capacity and toxicity; in contrast, polyanionic compounds are more ideal, among which composite phosphate cathode materials have attracted much attention.
[0004] Among composite phosphate cathode materials, pyrophosphate Na4Fe3(PO4)2P2O7 has attracted much attention due to its high theoretical capacity, suitable average voltage and good air stability. In addition, the material also has a three-dimensional framework for the free escape and embedding of Na ions, and its specific capacity is as high as 129 mAh g -1 , and is therefore regarded as an ideal cathode material with great commercial potential. However, despite the many advantages of phosphopyrophosphate Na4Fe3(PO4)2P2O7, its low electrochemical activity and insufficient conductivity limit the improvement of its specific capacity and rate performance, thus hindering the further development of this material.
[0005] Therefore, it is necessary to improve phosphate pyrophosphate materials. Summary of the invention
[0006] The purpose of the present application is to provide a sodium iron phosphate pyrophosphate positive electrode material, a preparation method thereof and a sodium ion battery, so as to solve the problem of low specific capacity and rate performance of existing sodium iron phosphate pyrophosphate positive electrode materials and improve the market competitiveness of sodium iron phosphate pyrophosphate positive electrode materials.
[0007] To achieve the above objectives, this application adopts the following technical solutions:
[0008] A sodium iron phosphate pyrophosphate positive electrode material comprises sodium iron phosphate pyrophosphate and a coating layer located on the outer surface of the sodium iron phosphate pyrophosphate, wherein the coating layer comprises conductive carbon and SiO2.
[0009] The present application also provides a method for preparing the sodium iron phosphate pyrophosphate positive electrode material as described above, comprising:
[0010] Mixing a sodium source, an iron source, a phosphorus source, SiO2, a composite carbon source and a dispersant, and vacuum drying to obtain a precursor material, wherein the composite carbon source includes an organic carbon source and an inorganic carbon source;
[0011] The precursor material is sintered in an inert atmosphere to obtain the sodium iron phosphate pyrophosphate positive electrode material.
[0012] According to an embodiment of the present application, the mass of the SiO2 accounts for 1wt%-5wt% of the total mass of all raw materials;
[0013] And / or, the mass of the composite carbon source accounts for 1wt%-4wt% of the total mass of all raw materials.
[0014] According to an embodiment of the present application, the organic carbon source includes at least one of glucose, sucrose, citric acid, polyvinyl alcohol, polyaniline, and polyacrylonitrile;
[0015] And / or, the inorganic carbon source includes at least one of graphite, activated carbon, and conductive carbon black;
[0016] And / or, the mass ratio of the inorganic carbon source to the organic carbon source is 1:(4-8).
[0017] According to an embodiment of the present application, the sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium citrate, sodium chloride, sodium hydroxide, sodium dihydrogen phosphate, and sodium pyrophosphate.
[0018] According to an embodiment of the present application, the iron source includes at least one of ferrous sulfate, ferrous gluconate, ferrous acetate, ferrous oxalate, and ferrous chloride.
[0019] According to an embodiment of the present application, the phosphorus source includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, and sodium pyrophosphate;
[0020] And / or, the dispersant includes an alcohol solvent, and the alcohol solvent includes ethanol.
[0021] According to an embodiment of the present application, the mixing method includes ball milling, the rotation speed of the ball mill is 580-620 r / min, and the time of the ball milling is 1-10 h.
[0022] According to an embodiment of the present application, the sintering temperature is 200-600° C., and the sintering time is 1-10 h;
[0023] And / or, the heating rate of the sintering is 1-10°C / min.
[0024] The present application also provides a sodium ion battery, which includes the sodium iron phosphate pyrophosphate positive electrode material described above or the sodium iron phosphate pyrophosphate positive electrode material prepared by the preparation method of the sodium iron phosphate pyrophosphate positive electrode material described above.
[0025] Compared with the prior art, the beneficial effects of this application include:
[0026] The SiO2 in the coating layer of the positive electrode material of the present application can separate the sodium iron pyrophosphate, further playing the role of refining the material size, and the conductive carbon in the coating layer can play the role of enhancing conductivity and improving rate performance. SiO2 and conductive carbon cooperate with each other to effectively improve the specific capacity and rate performance of the positive electrode material.
[0027] The present application can enhance the conductivity of the positive electrode material by adding a composite carbon source of an organic carbon source and an inorganic carbon source in the method for preparing the positive electrode material, thereby improving the problem of low specific capacity and rate performance of sodium iron phosphate pyrophosphate. At the same time, the present application also adds SiO2 with high temperature resistance in the method for preparing the positive electrode material, and SiO2 is evenly coated on the outer surface of sodium iron phosphate pyrophosphate, so that the active component of sodium iron phosphate pyrophosphate has a smaller particle size, and the synthesized phase is purer, which can reduce the occurrence of side reactions, and at the same time enhance the interaction between silicon dioxide and the active component iron interface, and obtain higher specific energy and better cycle stability. SiO2 and the composite carbon source cooperate with each other to improve the rate performance of the positive electrode material. Moreover, the method of the present application also has the advantages of simple operation, low cost, and green environmental protection.
[0028] The sodium ion half-battery of the present application has high specific energy, rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0030] Figure 1 This is a SEM image of the sodium iron pyrophosphate positive electrode material prepared in Example 1;
[0031] Figure 2 The first cycle charge-discharge curve of the sodium ion half-cell assembled with the positive electrode materials of the embodiment and the comparative example at 0.2C;
[0032] Figure 3 The rate performance diagram of the sodium ion half-cell assembled with the positive electrode materials of the embodiments of the present application and the comparative example;
[0033] Figure 4 This is a cycle diagram of a sodium ion half-cell assembled with the positive electrode material of Example 1 of the present application at 5C. DETAILED DESCRIPTION
[0034] As used herein:
[0035] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0036] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0037] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0038] In these examples, parts and percentages are by mass unless otherwise indicated.
[0039] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0040] “And / or” is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0041] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:
[0042] A sodium iron phosphate pyrophosphate positive electrode material comprises sodium iron phosphate pyrophosphate and a coating layer located on the outer surface of the sodium iron phosphate pyrophosphate, wherein the coating layer comprises conductive carbon and SiO2.
[0043] The SiO2 in the coating layer of the present application can separate the sodium iron pyrophosphate and play a role in refining the size of the material, and the conductive carbon in the coating layer can enhance the conductivity and improve the rate performance. SiO2 and conductive carbon cooperate with each other to effectively improve the specific capacity and rate performance of the positive electrode material.
[0044] The present application also provides a method for preparing a sodium iron phosphate pyrophosphate positive electrode material, comprising:
[0045] Mixing a sodium source, an iron source, a phosphorus source, SiO2, a composite carbon source and a dispersant, and vacuum drying to obtain a precursor material, wherein the composite carbon source includes an organic carbon source and an inorganic carbon source;
[0046] The precursor material is sintered in an inert atmosphere to obtain the sodium iron phosphate pyrophosphate positive electrode material.
[0047] During the sintering process, the high-melting-point SiO2 will not melt when the material is melted to form a new phase, and will act as a "boundary" to separate pieces of sodium iron phosphate pyrophosphate to achieve the effect of refining the size of the material. The conductive carbon formed after the mixed carbon source is sintered will also be separated by SiO2 and evenly coated on the sodium iron phosphate pyrophosphate, which will enhance the conductivity and improve the rate performance. In general, the preparation method of this application can be used to prepare a sodium iron phosphate pyrophosphate positive electrode material with the structure described above.
[0048] The present application adds a composite carbon source during the preparation process of the positive electrode material, which can enhance the conductivity of the positive electrode material and improve the problem of low specific capacity and rate performance of sodium iron phosphate pyrophosphate. At the same time, the present application adds SiO2 with high temperature resistance during the preparation process of the positive electrode material, which can make SiO2 uniformly coated on the outer surface of sodium iron phosphate pyrophosphate, so that the active component of sodium iron phosphate pyrophosphate has a smaller particle size, and the synthesized phase is purer, thereby reducing the occurrence of side reactions, while enhancing the interaction between silicon dioxide and the active component iron interface, and obtaining a higher specific energy and better cycle stability. The composite carbon source and SiO2 cooperate with each other, which significantly improves the rate performance of the positive electrode material. In addition, the present application method also has the advantages of simple operation, low production cost, and green environmental protection, and is suitable for large-scale promotion and application.
[0049] According to an embodiment of the present application, the mass of the SiO2 accounts for 1wt%-5wt% of the total mass of all raw materials;
[0050] According to some embodiments of the present application, the mass of SiO2 may account for 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any value between 1wt% and 5wt% of the total mass of all raw materials.
[0051] And / or, the mass of the composite carbon source accounts for 1wt%-4wt% of the total mass of all raw materials. Thus, the conductivity of the positive electrode material can be improved without affecting the capacity of the positive electrode material. If the amount of the composite carbon source added is too small, the conductivity of the positive electrode material will be improved to a small extent. If the amount of the composite carbon source added is too large, the content of the electrochemically active substance is relatively small, which will lead to incomplete capacity, reduce energy density, and affect the transmission of sodium ions.
[0052] According to some embodiments of the present application, the mass of the composite carbon source accounts for 1wt%, 2wt%, 3wt%, 4wt% or any value between 1wt% and 4wt% of the total mass of all raw materials.
[0053] The present application adopts an organic carbon source and an inorganic carbon source as a composite carbon source, which is more effective in improving the conductivity of the sodium iron pyrophosphate positive electrode material and the electrochemical performance of the battery compared with a single organic carbon source or a single inorganic carbon source coating.
[0054] Specifically, if a single organic carbon source is used for coating, since some water in the organic carbon source will evaporate or decompose gas to produce pores in the material during the melt carbonization process, it will have an adverse effect on the material coating effect and the pure phase of the material, and the carbon structure after carbonization is uncontrollable, which will lead to uncontrollable conductivity. If a single inorganic carbon source is used for coating, since the inorganic carbon source has a stable structure, it will not melt during the sintering process of the material but simply adhere to the surface of the sodium ferric phosphate pyrophosphate, which will cause the problem of unsatisfactory coating effect, and after a certain number of charge and discharge cycles, there will be a problem of poor capacity retention. The present application uses an organic carbon source and an inorganic carbon source as a composite carbon source. The organic carbon source can evenly coat the inorganic carbon source on the surface of the phosphate pyrophosphate material during the melt carbonization process, which can improve the undesirable problems of using a single organic carbon source or a single inorganic carbon source.
[0055] According to an embodiment of the present application, the organic carbon source includes at least one of glucose, sucrose, citric acid, polyvinyl alcohol, polyaniline, and polyacrylonitrile; these organic carbon sources can uniformly coat the inorganic carbon source on the surface of the sodium iron pyrophosphate material during the melt carbonization process.
[0056] And / or, the inorganic carbon source includes at least one of graphite, activated carbon, and conductive carbon black; these inorganic carbon sources have excellent electrical conductivity.
[0057] And / or, the mass ratio of the inorganic carbon source to the organic carbon source is 1:(4-8). When the mass of the organic carbon source to the inorganic carbon source is within the above range, the organic carbon source can have both conductive properties and a stable coating structure during the process of melting and carbonizing to carbon, so that the inorganic carbon source with controllable conductive capacity is orderly dispersed on the surface of the sodium iron phosphate pyrophosphate material, which has a good coating effect and is beneficial to improving the electrochemical performance of the positive electrode material.
[0058] If the mass of the organic carbon source is too much, there will be too many pores in the coating layer, resulting in poor coating effect and weak conductivity. If the mass of the inorganic carbon source is too much, the content of the organic carbon source is relatively small. Due to the small amount of organic carbon source melted, the inorganic carbon source cannot be evenly dispersed on the surface of the sodium iron pyrophosphate material.
[0059] According to some embodiments of the present application, the mass ratio of the inorganic carbon source to the organic carbon source may be 1:4, 1:5, 1:6, 1:7, 1:8 or any value between 1:(4-8).
[0060] According to an embodiment of the present application, the sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium citrate, sodium chloride, sodium hydroxide, sodium dihydrogen phosphate, and sodium pyrophosphate.
[0061] According to an embodiment of the present application, the iron source includes at least one of ferrous sulfate, ferrous gluconate, ferrous acetate, ferrous oxalate, and ferrous chloride.
[0062] According to an embodiment of the present application, the phosphorus source includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, and sodium pyrophosphate;
[0063] According to some embodiments of the present application, the amount of sodium source, iron source, and phosphorus source added is added according to the stoichiometric ratio of each element in Na4Fe3(PO4)2P2O7. Specifically, the ratio of the molar amount of sodium in the sodium source to the molar amount of iron in the iron source and the molar amount of phosphorus in the phosphorus source is 4:3:4.
[0064] And / or, the dispersant includes an alcohol solvent, and the alcohol solvent includes ethanol.
[0065] According to an embodiment of the present application, the mixing method includes ball milling, the rotation speed of the ball milling is 580-620 r / min, and the time of the ball milling is 1-10 hours. Under the above conditions, the uniformity of the mixing of the reaction raw materials can be improved, and the grains can be refined to ensure that the reaction raw materials have a suitable particle size, which is conducive to improving the electrochemical performance of the positive electrode material.
[0066] According to some embodiments of the present application, the rotation speed of the ball mill can be 580 r / min, 590 r / min, 600 r / min, 610 r / min, 620 r / min or any value between 580 and 620 r / min.
[0067] According to some embodiments of the present application, the ball milling time can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or any value between 1-10 h.
[0068] Furthermore, the ball milling equipment includes but is not limited to a planetary ball mill.
[0069] According to an embodiment of the present application, the sintering temperature is 200-600° C., and the sintering time is 1-10 h;
[0070] According to some embodiments of the present application, the sintering temperature may be 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or any value between 200-600°C.
[0071] According to some embodiments of the present application, the sintering time may be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or any value between 1-10 h.
[0072] And / or, the sintering is performed in an inert atmosphere; the inert atmosphere includes an argon atmosphere or a nitrogen atmosphere.
[0073] And / or, the heating rate of the sintering is 1-10°C / min. At the above heating rate, the grains can grow in an orderly manner as the temperature rises, which helps to form a uniform and dense microstructure, thereby improving the overall performance of the positive electrode material. If the heating rate is too fast or too slow, it will affect the crystallinity and thus the electrochemical performance of the positive electrode material.
[0074] According to some embodiments of the present application, the sintering heating rate can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or any value between 1-10°C / min.
[0075] The present application also provides a sodium ion battery, which comprises the sodium iron phosphate pyrophosphate positive electrode material described above or the sodium iron phosphate pyrophosphate positive electrode material prepared by the preparation method of the sodium iron phosphate pyrophosphate positive electrode material described above. The sodium ion battery has a high capacity, excellent rate performance and cycle stability.
[0076] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0077] 1. Preparation of Sodium Iron Phosphate Pyrophosphate Cathode Material
[0078] Example 1
[0079] Example 1 provides a sodium iron phosphate pyrophosphate positive electrode material, the preparation method of which includes:
[0080] Sodium carbonate: ferrous oxalate dihydrate: ammonium dihydrogen phosphate are weighed in a stoichiometric ratio of 2:3:4, and a composite carbon source and SiO2 are added. The composite carbon source includes graphite and citric acid. The amount of the composite carbon source added accounts for 3.5wt% of the total mass of all raw materials. The mass ratio of graphite to citric acid is 1:6 (the amount of graphite added accounts for 0.5wt% of the total mass of all raw materials, and the amount of citric acid added accounts for 3wt% of the total mass of all raw materials). The amount of SiO2 added accounts for 1wt% of the total mass of all raw materials. The mixture is ball-milled for 10 hours at a ball-milling speed of 600r / min, and the temperature is increased to 500°C at 2°C / min. It is sintered for 10 hours in an argon atmosphere to obtain a sodium iron pyrophosphate positive electrode material.
[0081] Figure 1 This is a SEM image of the sodium iron phosphate pyrophosphate positive electrode material prepared in Example 1. Figure 1 It can be seen that carbon and SiO2 are evenly coated on the surface of the sodium iron phosphate pyrophosphate material, and there is no excess coating material scattered, which proves that the coating effect is good. There are many fine spherical particles on the surface of the material agglomerate, which shows that the use of SiO2 to refine the size of the material has been successful. Thanks to the synergistic effect of organic carbon source and inorganic carbon source, less gas is generated during the carbonization process, resulting in fewer pores in the positive electrode material.
[0082] Example 2
[0083] The sodium iron phosphate pyrophosphate positive electrode material was prepared by referring to the method of Example 1. The preparation method of Example 2 is similar to that of Example 1, except that the added amount of the composite carbon source accounts for 1wt% of the total mass of all raw materials, and the other conditions are the same as those of Example 1.
[0084] Example 3
[0085] The sodium iron phosphate pyrophosphate positive electrode material was prepared by referring to the method of Example 1. The preparation method of Example 3 is similar to that of Example 1, except that the added amount of the composite carbon source accounts for 4wt% of the total mass of all raw materials, and the other conditions are the same as those of Example 1.
[0086] Example 4
[0087] The sodium iron phosphate pyrophosphate positive electrode material was prepared by referring to the method of Example 1. The preparation method of Example 4 is similar to that of Example 1, except that the added amount of SiO2 accounts for 5wt% of the total mass of all raw materials, and the other conditions are the same as Example 1.
[0088] Example 5
[0089] The sodium iron phosphate pyrophosphate positive electrode material was prepared by referring to the method of Example 1. The preparation method of Example 5 is similar to that of Example 1, except that the sintering time is 5 hours, and the other conditions are the same as those of Example 1.
[0090] Example 6
[0091] The sodium iron phosphate pyrophosphate positive electrode material was prepared by referring to the method of Example 1. The preparation method of Example 6 is similar to that of Example 1, except that the sintering conditions are different. Example 6 is first sintered at 200°C for 2h and then sintered at 600°C for 8h. The other conditions are the same as those of Example 1.
[0092] Comparative Example 1
[0093] The sodium iron phosphate pyrophosphate positive electrode material was prepared by referring to the method of Example 1. The preparation method of Comparative Example 1 was similar to that of Example 1, except that: Comparative Example 1 did not add graphite and SiO2, only citric acid was added, and the amount of citric acid added was 3wt% of the total mass of all raw materials. The other conditions were the same as Example 1.
[0094] Comparative Example 2
[0095] The sodium iron phosphate pyrophosphate positive electrode material was prepared by referring to the method of Example 1. The preparation method of Comparative Example 2 was similar to that of Example 1, except that: in Comparative Example 2, no graphite and citric acid were added, and only SiO2 was added, and the amount of SiO2 added was 1wt% of the total mass of all raw materials. The other conditions were the same as those of Example 1.
[0096] Comparative Example 3
[0097] The sodium iron phosphate pyrophosphate positive electrode material was prepared by referring to the method of Example 1. The preparation method of Comparative Example 3 was similar to that of Example 1, except that: Comparative Example 3 did not add SiO2 and citric acid, only added graphite, and the amount of graphite added was 0.5wt% of the total mass of all raw materials. The other conditions were the same as Example 1.
[0098] Comparative Example 4
[0099] The sodium iron phosphate pyrophosphate positive electrode material was prepared by referring to the method of Example 1. The preparation method of Comparative Example 4 was similar to that of Example 1, except that: Comparative Example 4 did not add SiO2, but only added graphite and citric acid, and the added amounts of graphite and citric acid were 0.5wt% and 3wt% of the total mass of all raw materials, respectively, and the other conditions were the same as those of Example 1.
[0100] Comparative Example 5
[0101] Sodium iron phosphate pyrophosphate positive electrode material was prepared by referring to the method of Example 1. The preparation method of Comparative Example 5 was similar to that of Example 1, except that: in Comparative Example 5, citric acid was not added, and only graphite and SiO2 were added. The addition amounts of graphite and SiO2 were 0.5wt% and 1wt% of the total mass of all raw materials, and the other conditions were the same as those of Example 1.
[0102] Comparative Example 6
[0103] The sodium iron phosphate pyrophosphate positive electrode material was prepared by referring to the method of Example 1. The preparation method of Comparative Example 6 was similar to that of Example 1, except that no graphite was added to Comparative Example 6, and only SiO2 and citric acid were added. The added amounts of SiO2 and citric acid were 1wt% and 3wt% of the total mass of all raw materials, respectively. The other conditions were the same as those of Example 1.
[0104] 2. Electrochemical performance test of sodium iron pyrophosphate positive electrode material
[0105] (1) Preparation of positive electrode sheet: Slurry was prepared according to the ratio of positive electrode active material: conductive agent: binder = 8:1:1. The sodium iron phosphate pyrophosphate positive electrode material prepared in the embodiment or comparative example was used as the positive electrode active material, PVDF as the binder, and Super P as the conductive agent. First, 25 mg of PVDF was weighed and placed in a weighing bottle, and 800 μL of NMP was added dropwise. The weighing bottle was sealed with plastic wrap and stirred with a magnetic stirrer for 6 h. After stirring, the plastic wrap was opened, and 200 mg of sodium iron phosphate pyrophosphate positive electrode material and 25 mg of Super P were added and stirred for 6 h. The prepared slurry was evenly coated on aluminum foil using a coating machine. After coating, it was placed in a 90°C vacuum drying oven for drying for 6 h. After drying, it was taken out and cut into pieces using a cutting machine to obtain positive electrode sheets.
[0106] (2) Assembly of half-cell: The prepared positive electrode sheet is used as the positive electrode, the sodium sheet is used as the negative electrode, the battery shell model is 2025, the electrolyte is 1 mol / L NaPF6, the solvent is a mixed solvent of EC and DMC in a volume ratio of 1:1, and FEC accounting for 5% of the total volume of the electrolyte is added as a film-forming additive. The separator is glass fiber for half-cell assembly.
[0107] (3) Electrochemical performance test: The battery was placed in a battery constant temperature test system for constant current charge and discharge test. The test conditions were: voltage range: 1.7 V-3.5 V, rate: 0.2 C, 1 C, 2 C, 5 C (where the current density of 1 C is 129 mA / g). The test results are shown in Table 1.
[0108] Table 1 Rate performance of sodium ion half-cells in the embodiments and comparative examples
[0109] 0.2C 1C 2C 5C Example 1 Specific capacity (mAh / g) 103.8 102.48 101.82 100.4 Example 2 Specific capacity (mAh / g) 87.18 86.22 85.18 83.43 Example 3 Specific capacity (mAh / g) 89.93 87.47 86.32 82.37 Example 4 Specific capacity (mAh / g) 101.72 99.10 98.01 96.11 Example 5 Specific capacity (mAh / g) 94.58 91.81 90.37 87.32 Example 6 Specific capacity (mAh / g) 95.66 92.13 90.33 86.81 Comparative Example 1 Specific Capacity (mAh / g) 61.28 57.4 54.35 48.5 Comparative Example 2 Specific Capacity (mAh / g) 55.52 24.45 11.99 2.02 Comparative Example 3 Specific Capacity (mAh / g) 74.93 59.22 52.23 40.41 Comparative Example 4 Specific Capacity (mAh / g) 89.33 73.58 67.55 57.58 Comparative Example 5 Specific Capacity (mAh / g) 89.48 86.02 83.85 78.86 Comparative Example 6 Specific Capacity (mAh / g) 91.27 75.09 68.73 47.78
[0110] From Table 1 and Figure 2 , Figure 3 It can be seen that the specific capacity and rate performance of Comparative Examples 1-6 are both poor. Compared with Comparative Examples 1-6, Examples 1-6 have excellent rate performance and specific capacity.
[0111] Figure 4 is the cycle diagram of the sodium ion half-cell of Example 1 of the present application at 5C, Figure 4 It can be seen that after 860 cycles, the capacity retention rate of Example 1 is still as high as 90.14%, indicating that the positive electrode material of Example 1 has excellent cycle performance.
[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0113] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A sodium iron phosphate pyrophosphate positive electrode material, characterized in that: The invention comprises sodium ferric pyrophosphate phosphate and a coating layer located on the outer surface of the sodium ferric pyrophosphate phosphate, wherein the coating layer comprises conductive carbon and SiO2.
2. A method for preparing the sodium iron phosphate pyrophosphate positive electrode material as claimed in claim 1, characterized in that: include: Mixing a sodium source, an iron source, a phosphorus source, SiO2, a composite carbon source and a dispersant, and vacuum drying to obtain a precursor material, wherein the composite carbon source includes an organic carbon source and an inorganic carbon source; The precursor material is sintered in an inert atmosphere to obtain the sodium iron phosphate pyrophosphate positive electrode material.
3. The method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to claim 2, characterized in that: The mass of SiO2 accounts for 1wt%-5wt% of the total mass of all raw materials; And / or, the mass of the composite carbon source accounts for 1wt%-4wt% of the total mass of all raw materials.
4. The method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to claim 3, characterized in that: The organic carbon source includes at least one of glucose, sucrose, citric acid, polyvinyl alcohol, polyaniline, and polyacrylonitrile; And / or, the inorganic carbon source includes at least one of graphite, activated carbon, and conductive carbon black; And / or, the mass ratio of the inorganic carbon source to the organic carbon source is 1:(4-8).
5. The method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to claim 2, characterized in that: The sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium citrate, sodium chloride, sodium hydroxide, sodium dihydrogen phosphate, and sodium pyrophosphate.
6. The method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to claim 2, characterized in that: The iron source includes at least one of ferrous sulfate, ferrous gluconate, ferrous acetate, ferrous oxalate and ferrous chloride.
7. The method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to claim 2, characterized in that: The phosphorus source includes at least one of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, and sodium pyrophosphate; And / or, the dispersant includes an alcohol solvent, and the alcohol solvent includes ethanol.
8. The method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to claim 2, characterized in that: The mixing method includes ball milling, the rotation speed of the ball mill is 580-620 r / min, and the time of the ball milling is 1-10 h.
9. The method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to any one of claims 2 to 8, characterized in that: The sintering temperature is 200-600°C, and the sintering time is 1-10h; And / or, the heating rate of the sintering is 1-10°C / min.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium iron phosphate pyrophosphate positive electrode material according to claim 1 or the sodium iron phosphate pyrophosphate positive electrode material prepared by the method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to any one of claims 2-9.
Citation Information
Cited By
Doped and coated ferric sodium pyrophosphate positive electrode material, preparation method thereof and battery
CN121651315A
Nitrogen and phosphorus co-doped carbon-coated positive electrode material of NaFePO4F, and preparation method and application of nitrogen and phosphorus co-doped carbon-coated positive electrode material
CN122291476A